Risks and Vulnerabilities in the U.S. Bond Mutual Fund Industry - Bouveret, Antoine (IMF Working Papers; Working Paper, 2021)
This paper assesses liquidity risk for the United States (U.S.) bond mutual funds industry and performs a range of analyses to identify which fund categories are more vulnerable to distress than others, and how sales from funds can impact financial stability. We develop a new measure to identify vulnerable categories based on expected outflows labelled 'Flows in Distress'. Overall, most U.S. mutual funds are resilient yet high yield (HY) and loan funds would face a liquidity shortfall when faced with severe redemption shocks. Combined sales from funds can have a sizeable price impact. Finally, our contagion analysis using data on fund flows and returns shows that Investment Grade (IG) corporate bonds funds, municipal bond funds and government bond funds are more likely to spread distress to other fund categories than HY, EM and loan funds. When the first type of funds experiences stress, other funds categories are likely to experience stress as well.